2023
DOI: 10.3233/jad-220829
|View full text |Cite
|
Sign up to set email alerts
|

Pathological (Dis)Similarities in Neuronal Exosome-Derived Synaptic and Organellar Marker Levels Between Alzheimer’s Disease and Frontotemporal Dementia

Abstract: Background: Alzheimer’s disease (AD) and frontotemporal dementia (FTD) are pathologically distinct neurodegenerative disorders with certain overlap in cognitive and behavioral symptoms. Both AD and FTD are characterized by synaptic loss and accumulation of misfolded proteins, albeit, in different regions of the brain. Objective: To investigate the synaptic and organellar markers in AD and FTD through assessment of the levels of synaptic protein, neurogranin (Ng) and organellar proteins, mitofusin-2 (MFN-2), ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Exosomal contents can be used as biomarkers to differentiate AD from normal controls, MCI as well as other forms of dementia such as fronto-temporal dementia. In a study by Krishna et al, 160 the synaptic and organellar markers in AD and frontotemporal dementia (FTD) are investigated by assessing the levels of synaptic protein, neurogranin (Ng), and organellar proteins, mitofusin-2 (MFN-2), lysosomal associated membrane protein-2 (LAMP2), and golgin A4 from neuronal exosomes. Exosomes obtained from the plasma of healthy controls (HC), AD and FTD subjects were analyzed.…”
Section: Role Of Exosomes In Ad Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomal contents can be used as biomarkers to differentiate AD from normal controls, MCI as well as other forms of dementia such as fronto-temporal dementia. In a study by Krishna et al, 160 the synaptic and organellar markers in AD and frontotemporal dementia (FTD) are investigated by assessing the levels of synaptic protein, neurogranin (Ng), and organellar proteins, mitofusin-2 (MFN-2), lysosomal associated membrane protein-2 (LAMP2), and golgin A4 from neuronal exosomes. Exosomes obtained from the plasma of healthy controls (HC), AD and FTD subjects were analyzed.…”
Section: Role Of Exosomes In Ad Diagnosismentioning
confidence: 99%
“…Crucially, alterations in the levels of synaptic protein, neurogranin (Ng) and MFN-2, LAMP2, and golgin A4 from neuronal exosomes are helpful to distinguish AD from normal controls and FTD. 160 The two-stage-sectional investigation by Jia et al 161 examined the potential of exosomal synaptic proteins as a predictor of asymptomatic Alzheimer’s disease. The first trial included participants with preclinical AD and controls, while the second study confirmed the findings in familial AD.…”
Section: Role Of Exosomes In Ad Diagnosismentioning
confidence: 99%
“…Guo and team [32] highlight the novel roles of meningeal lymphatic vessels in AD, while Zhang et al [33] highlight the significant role of necroptosis in AD and its relevance for novel biomarker discovery and future drug targets. Krishna and colleagues [34] provide new dimensions on pathological dissimilarities in neuronal exosome-derived synaptic networking between AD and frontotemporal dementia. Additionally, Naren et al [35] give insights into the key role of mitochondria health in brain disorders and provide new ideas on mitochondrial integrity and healthy functional mitochondria as key in brain health.…”
Section: Theme 4: New and Novel Metabolic Pathways In Neuronal Cell D...mentioning
confidence: 99%